Digital platform-based ecosystems: the evolution of collaboration and competition between incumbent producers and entrant platforms - Cozzolino, Alessio (2021)
The rise of the Internet has seen traditional incumbent producers challenged by competition from digital entrant platforms. It is unclear, however, how those two types of actors—which are in competition but also mutually dependent—can co-exist in the new platform-based ecosystem. This paper sheds light on that pivotal phenomenon by connecting the traditional literature on incumbent adaptation with the growing conversation on digital platform-based ecosystems. Through a qualitative longitudinal (2005–2019) study of the global digital advertising ecosystem, we examine how incumbent producers pivot between competitive and cooperative strategies in response to digital entrant platforms. Our analysis reveals a process characterized by three sequential phases: (1) selective cooperation, (2) allied competition, and (3) selective coopetition. Those phases show how switching between different multi-level strategies spanning market segments, products, and technological components represents a viable solution for incumbent producers adapting in the face of entrant platforms.